Effects of nutrient enrichment and activity of invertebrate shredders on leaf litter breakdown in low order streams. Issue 4 (24th July 2013) - Fleituch, Tadeusz
Abstract This study compares leaf breakdown rates of two common plant species (alder and oak) in pristine and low‐to‐moderately polluted streams and investigates changes in the functioning of invertebrate consumers across the Western Carpathians (Poland). No positive effect of elevated nutrient concentration on litter breakdown rates was observed regardless of leaf species and litter bag mesh size. The litter breakdown rate was low at impacted sites, which was probably due to the combined effect of toxic compounds in waste water and oxygen depletion. Small shredders (e.g. stoneflies) were most abundant in pristine streams. In contrast, in some impacted streams larger gammarids or dipterans were more abundant. Shredder densities in the two stream types did not differ significantly but the diversity of shredders was significantly lower in impacted streams. Dipterans preferred more alder than oak litter. Feeding behavior of gammarids and dipterans in impacted streams may reflect their specific physiological adaptation of alimentary canals for food assimilation. Changes in impacted stream ecosystems were better explained by modifications in the shredder composition than by changes in litter breakdown rates.